2017
DOI: 10.1016/j.chembiol.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome Activation by Small Molecules

Abstract: Drugs that increase 26S proteasome activity have potential therapeutic applications in the treatment of neurodegenerative diseases. A chemical genetics screen of over 2,750 compounds using a proteasome activity probe as a readout in a high-throughput live-cell fluorescence-activated cell sorting-based assay revealed more than ten compounds that increase proteasome activity, with the p38 MAPK inhibitor PD169316 being one of the most potent ones. Genetic and chemical inhibition of either p38 MAPK, its upstream r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
108
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 52 publications
2
108
0
1
Order By: Relevance
“…We first established that proteasome activity could be modulated in CD8 + T cells with the pan-subunit proteasome inhibitor epoxomicin ( Figure 2A). We then screened a panel of proteasome activators that has been shown to increase proteasome activity in immortalized cell lines (30). Several of these compounds also increased proteasome activity in CD8 + T cells ( Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first established that proteasome activity could be modulated in CD8 + T cells with the pan-subunit proteasome inhibitor epoxomicin ( Figure 2A). We then screened a panel of proteasome activators that has been shown to increase proteasome activity in immortalized cell lines (30). Several of these compounds also increased proteasome activity in CD8 + T cells ( Figure 2A).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that cells treated with proteasome inhibitor exhibited an enhanced capacity to produce IFN-γ relative to control-treated cells ( Figure 2C), while one of the proteasome activators we tested (activator 9) reduced cytokine production by CD8 + T cells; we selected this proteasome activator, revealed to be cyclosporine, for subsequent experiments. The activators we tested were identified in a high-throughput screen solely based on their ability to increase proteasome activity (30); thus, they may act through different mechanisms and have unique functional properties. segregation within mitotic CD8 + T cells (11), led us to hypothesize that proteasome activity may be an important regulator of CD8 + T lymphocyte fate specification.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there was an accumulation of certain short-lived proteins that normally undergo proteasomal degradation by ubiquitin-dependent (GFPu, UbG767V-GFP) or independent (ODC-GFP) routes (80). Conversely, siRNA-mediated knockdown of endogenous ASK1 enhanced proteasomal peptidase activity and the degradation of these proteins in HEK293 cells, mouse embryonic fibroblasts, and human melanoma cells (80, 82). Thus in these cultures, endogenous ASK1 appears to cause some basal phosphorylation of the 26S proteasome that limits its activity and inhibits intracellular proteolysis.…”
Section: Apoptosis Signal-regulating Kinase 1 (Ask1) and Proteasome Imentioning
confidence: 99%
“…In addition to ASK1, other kinases in the p38 MAPK signaling cascade can repress proteasome function (82, 84). Overexpression of an active mutant of p38 MAPK caused the accumulation of proteins that normally undergo rapid proteasomal degradation by ubiquitin-dependent (GFPu, UbG767V-GFP, Ub-R-GFP) or independent (ODC-GFP) routes (84).…”
Section: Apoptosis Signal-regulating Kinase 1 (Ask1) and Proteasome Imentioning
confidence: 99%
“…Rolipram inhibits phosphodiesterase 4 thus activating protein kinase A to enhance proteasome activity and in a HD mouse model was shown to alleviate symptoms of neuronal dysfunction 93 . Recently, a series of compounds which enhance proteasome activity were identified using a UPS activity probe 94,95 with p38 MAPK inhibitor PD169316 proving the most potent. Activation of the UPS with these small molecules showed increased proteasome activity and aggregate clearance in a Parkinson's disease model.…”
Section: Therapeutic Approaches In Hd Targeting Upsmentioning
confidence: 99%